2020
DOI: 10.1111/jocn.15566
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia, fatigue and psychosocial well‐being during COVID‐19 pandemic: A cross‐sectional survey of hospital nursing staff in the United States

Abstract: Aims and objectives To describe the levels of insomnia, fatigue and intershift recovery, and psychological well‐being (burnout, post‐traumatic stress and psychological distress), and to examine differences in these measures based on work‐related characteristics among nursing staff during COVID‐19 pandemic in the United States. Background The COVID‐19 pandemic has created a major physical and psychological burden on nursing staff in the United States and worldwide. A bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

30
221
1
23

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(275 citation statements)
references
References 60 publications
30
221
1
23
Order By: Relevance
“…During the early stages of the COVID-19 epidemic, HCWs often worked longer each day. Under these circumstances, breaks were crucial to alleviating fatigue (39). In line with previous research, insomnia symptoms and feelings of fatigue were found to be inversely correlated with sleep duration (40).…”
supporting
confidence: 85%
“…During the early stages of the COVID-19 epidemic, HCWs often worked longer each day. Under these circumstances, breaks were crucial to alleviating fatigue (39). In line with previous research, insomnia symptoms and feelings of fatigue were found to be inversely correlated with sleep duration (40).…”
supporting
confidence: 85%
“…Similar findings have been demonstrated in the context of healthy lifestyle behaviours at work (e.g., physical activity), where job-related barriers to engagement in health behaviours included the structure and nature of the working day (high workload, front line job requirements), workplace culture and norms (resentment from colleagues, no break culture) and organizational concerns (cost of lost time, public perceptions) [ 65 ]. Lack of work breaks and an absence of suitable rest areas is particularly common amongst healthcare workers [ 66 , 67 , 68 , 69 ], although it is well-established that long hours and consecutive shifts without breaks have negative psychological impacts, and health and safety implications for healthcare workers and patients [ 23 , 70 ]. Within-day work breaks can reduce fatigue and negative emotions [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Open access very experienced, having worked in the NHS for many years and have previously reported higher levels of job satisfaction and well-being than other areas of the NHS. 19 Increased fear due to the pandemic has been associated with higher levels of burnout in Spain, 22 decreased psychological well-being in the USA 23 and higher intention to leave in the Philippines. 24 Studies in China and Iran have already shown that healthcare staff who are not properly equipped in this crisis are at high risk of mental health conditions such as depression, anxiety and post-traumatic stress disorder.…”
Section: Discussionmentioning
confidence: 99%